The Impact of non-curricular coaching in finance and marketing on final-year entrepreneurial university students in Manta, Manabí - Andrade Navarrete, Mario; Tigua Tobar, Danny (Revista Internacional de Estudios en Ciencias Administrativas STRATEGOS, 2026)
This study analyzes the impact of non-curricular coaching on the development of financial and marketing competencies in final-year entrepreneurial university students in Manta, Manabí. A quantitative, non-experimental, cross-sectional, and correlational-explanatory design was applied, using a structured Likert-scale survey administered to 588 students from three private universities. Descriptive statistics revealed that coaching dimensions, particularly personalized feedback and financial guidance, were rated higher than competency development levels. A structural equation model (SEM) was estimated to evaluate the relationship between variables. The results showed adequate model fit in incremental indices (CFI = 0.945; TLI = 0.920) and low residual error (SRMR = 0.030), confirming the consistency of the measurement model. The structural analysis supports that non-curricular coaching positively influences financial decision-making and entrepreneurial performance, although its impact on marketing competencies remains moderate. The findings highlight the importance of integrating structured coaching strategies into higher education to strengthen applied entrepreneurial skills.
Keywords: Non-curricular coaching; entrepreneurial competencies; financial decision-making; marketing skills